Biomechanical abdominal wall model applied to hernia repair. Issue 2 (27th January 2015) - Lyons, M; Mohan, H; Winter, D C; Simms, C K
Abstract: Background: Most surgical innovations require extensive preclinical testing before employment in the operative environment. There is currently no way to develop and test innovations for abdominal wall surgery that is cheap, repeatable and easy to use. In hernia repair, the required mesh overlap relative to defect size is not established. The aims of this study were to develop a biomechanical model of the abdominal wall based on in vivo pressure measurements, and to apply this to study mesh overlap in hernia repair. Methods: An observational study of intra-abdominal pressure (IAP) levels throughout abdominal surgery was conducted to identify the peak perioperative IAP in vivo . This was then applied in the development of a surrogate abdominal wall model. An in vitro study of mesh overlap for various defect sizes was then conducted using this clinically relevant surrogate abdomen model. Results: The mean peak perioperative IAP recorded in the clinical study was 1740 Pa, and occurred during awakening from anaesthesia. This was reproduced in the surrogate abdomen model, which was also able to replicate incisional hernia formation. Using this model, the mesh overlap necessary to prevent hernia formation up to 20 kPa was found, independent of anatomical variations, to be 2 × (defect diameter) + 25 mm. Conclusion: This study demonstrated that a surgically relevant surrogate abdominal wall model is a useful translational tool in the study of hernia repair. Surgical relevance This study examined the mesh overlap requirements for hernia repair, evaluated in a biomechanical model of the abdomen. Currently, mesh size is selected based on empirical evidence and may underpredict the requirement for large meshes. The study proposes a relationship between the defect size and mesh size to select the appropriate mesh size. Following further trials and investigations, this could be used in clinical practice to reduce the incidence of hernia recurrence. Abstract : Useful translational tool